Effect of Complex Training and Resistance Running Program on 100- Meters Race Performance of Men Sprinters: The Impact of Complex Training and Resistance Running on Sprinters' 100-Meter Dash Performance (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The present study was undertaken to analyze the impact of complex training and resistancerunning program on 100- meters race performance of men sprinters. Total N=60 (sixty) male engineeringstudents age ranging from 18-21 years selected from various branches of Indian Institute of TechnologyKanpur, Uttar Pradesh, India. The chosen sprinters were assigned into four subgroups by the equatedgroup design on the bases of 100 meters run result performance. The subgroups namely empiricalgroup – I considered as complex training group [CTG = 15], empirical group –II considered as resistancerunning program group [RRG =15], empirical group – III combined complex training resistance runningprogram group [CCR=15] and control [CG=15] group – IV were restricted from taking part any specificcoaching program (Under observation). The training period was for a twelve weeks. The data werecollected before and after the training by conducting 100 meter test. The obtained data‟s were analyzedby Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of thestudy showed that that complex training, resistance running program and combined complex trainingand resistance running program were effective to increase the speed of 100 – meter dash performance ofsprinters comparative to control group.